Eloise made these steps well:
Square root of negative 2x plus 1 - 3 = x
Square root of negative 2x plus 1 - 3 + 3 = x + 3
The error comes in the next step:
Square root of negative 2x plus 1 = x + 3
Square root of negative 2x plus 1 -1 = x + 3 - 1
Square root of negative 2x = x + 2
the number one is inside the root, therefore they can not be subtracted.
answer
error in the step:
Square root of negative 2x = x + 2
The hypotenuse is equal to the square of the other two sides. The length of AC from the diagram is 21.9feet
<h3>Application of pythagoras theorem</h3>
The theorem states that the square of the hypotenuse is equal to the square of the other two sides
Given the following
Hypotenuse = 26 feet = CD
Base side = AD = 14ft
Required
Length AC
Use the theorem
26^2 = 14^2 + AC^2
AC^2 = 676 - 196
AC^2 = 480
AC = 21.9feet
Hence the length of AC from the diagram is 21.9feet
Learn more on pythagoras theorem here: brainly.com/question/343682
Answer:
Just Multiply them together
Step-by-step explanation:
Answer:
![DM=12](https://tex.z-dn.net/?f=DM%3D12)
Step-by-step explanation:
(Let the point where the altitude from
intersects
be called as point
.) First, let's find the area of parallelogram
. The area of a parallelogram is simply
, where
is the parallelogram's base and
is the parallelogram's height. If we let
and
be the base and height respectively, since we are already given their lengths, we know that the area of parallelogram
will be
.
Now, how does this information matter, you might ask? Well, we can take either
<em>or </em>
to be the base and either
or
to be the height. In this case, let's take the latter two options, as we are looking to find the length of
.
Therefore, we know that the area of parallelogram
can also be found by calculating
. Since we know the values of the area and
, we can write the following equation to solve for
:
![Area = CB*DM](https://tex.z-dn.net/?f=Area%20%3D%20CB%2ADM)
(Substitute
and
into the equation)
(Divide both sides of the equation by
to get rid of
's coefficient)
(Simplify)
(Symmetric Property of Equality)
Hope this helps!
Answer: Since each recipe makes 28 cookies, tripling the recipe would give him 28(3) = 84 cookies.
Step-by-step explanation: <em>Since each recipe makes 28 cookies, tripling the recipe would give him 28(3) = 84 cookies.
</em>
<em>
</em>
<em>Then divide the total number of cookies by the number of guests: 84 21 = 4. Each person would get 4 cookies.</em>
<em>
</em>
<em>This process can be modeled by the expressions 28(3) ÷ 21 and </em>
<em>28(3)
</em>
<em>21
</em>
<em>. This is because the fraction bar represents division.</em>